Sport results, training loads and physical ability change of young high performance female ski racers in 16-20 years of age - Cepulenas, A. (8th International Sports Science Conference, Vilnius, 25-26 February 2005, 2002)
The aim of the study was to analyze the change of sport results, training loads, and physical and functional abilities of I.T, the most powerful Lithuania cross country ski racer, during 2000-2004 year period and to determine advantages and weaknesses of her sport preparedness. Generalization of the results: Performed cyclic loads of the ski racer were the heaviest during 2002-2003 year season, but during 2003-2004 year cycle - have reduced. On purpose to achieve sport results upturn, it is necessary to plan more rationally training loads according to intensity zones and specificity of training appliances. The ski racer`s aerobic capacity is big, but it is necessary to increase aerobic power.